CORRELATION OF MIGRATORY ATTITUDES OF MAGADAN INHABITANTS AND FEATURES OF THEIR DEFENSIVE-COPING BEHAVIOUR - Snezhana A Kuznetsova (Peoples' Friendship University of Russia (RUDN University), 2017)
The results of the empirical research of the correlation between the migratory attitudes of the inhabitants of Magadan and the features of their defensive-coping behavior are described in the article. Methods: the author's scale of migratory attitudes of the personality, the scale of situational and personal anxiety by C.Spilberger, questionnaires "Life style index" (LSI), "Strategic Approach to Coping Scale" (SACS). The research with the participation of 68 Magadan inhabitants has shown that the inhabitants with the low level of personal anxiety, using regression as a defense mechanism, the coping forms: avoidance, indecisive actions and passive forms of coping behavior as a whole, have less expressed migratory attitudes. And on the contrary, the migratory attitudes are more likely to form in the respondents who are ready for active, resolute, constructive actions to change an unsatisfyingsituation, seek social support, take into account the needs, opinions and expectations of the immediate social environment. However, the correlations of migratory attitudes with the active forms of coping are not revealed. It means that the activity inherent in the subject does not necessarily imply a desire of migration, and can be implemented in the current region of residence.